Purchase Decision of Fresh Fish at Paotere Fish Auction Place (TPI) during Covid-19 Pandemic, Makassar City - Aynun, Nur Citra; Amri, Andi; Gosari, Benny Audy Jaya; Amiluddin, Amiluddin; Hamzah, Hamzah (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
This study aims to determine the factors that influence fresh fish purchasing decisions and determine the characteristics of fresh fish consumers at TPI Paotere during the Covid-19 pandemic, Makassar City using the factor analysis method. This research was conducted at Paotere Fish Auction Place in Makassar City from March to April 2021. The sampling method uses nonprobability sampling technique with accidental sampling method with a sample size of 100 respondents. The data analysis used is factor analysis and the KMO and Barlett's Test. The results showed that there are 6 dominant factors consisting of 18 variables that influence the decision to buy fresh fish at TPI Paotere during the Covid-19 pandemic. The dominant factors influencing fresh fish purchase decisions at TPI Paotere during the Covid-19 pandemic consist of personal factors consisting of lifestyle variables, role and status in the family, price, social class standards, easy payment, and habits; Covid-19 pandemic factors consisting of supply variables during the pandemic, New Normal, and nutritional needs during the pandemic; location factors consisting of the largest fish market variables, fish quality, convenient location; and diversity of fish types, social environment factors consisting of family influence and friend influence variables; respondent characteristics factors consisting of age and occupation / position variables; and service factors consisting of service variables.